Numerical study of stress analysis for the different widths of padding welds - Kulawik, Adam (Strojniški vestnik, 2020)
In the presented study, the cases of regeneration of the element made of C45 steel, using the MAG (Metal Active Gas) method are analysed. The base material is applied to the regeneration process. The analysis of the influence of the padding weld width (0.006 m, 0.01 m, 0.014 m) and the preheating temperature on the phase transformations and effective stresses of the regenerated layer are performed. A nonstandard approach to preheating (before each padding weld after the cooling to ambient temperature) is considered. Due to the possibility of simplifying the model from 3D to 2D (symmetry of calculations for long padding welds), calculations were performed using the finite element method in the transverse to the padding direction. Each new padding weld was included as an additional area in the finite element mesh. The developed numerical model includes a temperature model, phase transformations in the liquid and solid states, and the stress model in the elastic-plastic range. The aim of the regeneration is not only to obtain the original geometry of the element, but it is also important that the filler material used (in the considered case identical to the base material) has appropriate properties. These properties largely depend on the phase composition. The used filler material affects not only the hardness, brittleness, and ductility of the material. Its kinetics and changes in the geometry can cause significant stresses and even cracks. Based on the obtained results, it can be concluded that increasing the width of the padding welds causes a decrease in the level of residual effective stress; however, it is technologically difficult to accomplish. The most unfavourable stresses occur in the initial area of the pad welding zone. For lower preheating temperatures and smaller welds, areas with possible cracks are identified. In these cases, lower preheating and tempering should be carried out, which leads to similar energy costs as at higher preheating temperatures. Due to the complex phase transformation process for medium carbon steels and the need for the process parameters control, proper regeneration is possible only in automated workstations.
Keywords: analiza deformacij; computational mechanics; napetost; navar; numerical simulation; numerična simulacija; padding weld; predgrevanje; preheating; računalniška mehanika; strain analysis; stress